Mengembangkan Moderasi Beragama Berorientasi Pada Kearifan Lokal Dayak Bahau Bateq - Novianus Isang; Silpanus Dalmasius (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2021)
This study aims to describe the concept or view of religious moderation that is accommodative to local culture. In addition, to describe the implementation of local wisdom of Dayak Bahau Bateq which can be used as a reference to develop the practice of religious moderation. This study uses a qualitative approach with the method of observation, literature study and interviews for data collection. Practicing religious moderation that is accommodative to local culture is actually an effort to maintain inter-religious harmony so that the living conditions of the nation and society are always peaceful and tolerant. The practice of religious moderation is always correlated with culture, especially because everything in society is determined by the culture that is owned by the community. Local wisdom is manifested in local knowledge, local intelligence and local symbols. The local wisdom of the Dayak Bahau Bateq can be used as a reference for orientation to develop religious moderation which is currently experiencing various threats. The practice of religious moderation, which is accommodative to culture, always has a correlation with the practice of local wisdom.